2020
DOI: 10.33373/sim-bio.v9i2.2498
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Mangrove dan Pemanfaatannya di Desa Daiama, Kecamatan Landu Leko, Kabupaten Rote Ndao, Propinsi Nusa Tenggara Timur

Abstract: Mangrove merupakan ekosistem utama pendukung kehidupan yang penting di wilayah pesisir dan lautan. Jenis-jenis mangrove di Desa Daiama khususnya Pulau Rote, pulau paling selatan Indonesia sampai saat ini belum diinventarisasi. Penelitian ini bertujuan untuk mengetahui struktur vegetasi mangrove dan pemanfaatannya di Desa Daiama, Kecamatan Landu Leko, Kabupaten Rote Ndao. Teknik pengumpulan data struktur vegetasi mangrove dilakukan dengan membuat peletakan sebanyak plot 16 pada 4 stasiun. Penempatan plot dilaku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This fungus has thin-walled conidiophores. (Saru, et al, 2019) and in Rote Ndao, East Nusa Tenggara, 11 species were found (Ngoma, et al, 2020). It provides an opportunity to utilize mangrove species for treatment, for example as an antibacterial.…”
Section: Testing the Antibacterial Activity Of Mangrove Endophytic Fungi Againstmentioning
confidence: 99%
“…This fungus has thin-walled conidiophores. (Saru, et al, 2019) and in Rote Ndao, East Nusa Tenggara, 11 species were found (Ngoma, et al, 2020). It provides an opportunity to utilize mangrove species for treatment, for example as an antibacterial.…”
Section: Testing the Antibacterial Activity Of Mangrove Endophytic Fungi Againstmentioning
confidence: 99%